Tiepoints data correlating the depth domain from core GLAD6 BOS04 5B to the age domain of the Iberian Margin Sea Surface Temperature record - Mathias Vinnepand; Christian Zeeden; Thomas Wonik; William D Gosling; Anders Noren; Jochem Kück; Simona Pierdominici; Silke Voigt; Mehrdad Sadar Abadi; Arne Ulfers; Sylvester Danour; Kweku Afrifa; et al. (PANGAEA, 2024)
This dataset was created in the framework of the REFINE project aiming to establish an age-depth model for Lake Bosumtwi (Ghana, West Africa) that bases on a combination of cyclostratigraphy and correlation analyses. For creating our age-depth model, the NGR data of core GLAD6 BOS04 5B have been smoothed using a 35 point mean and were correlated to Iberian Margin Sea Surface Temperatures. For this, a suite of tiepoints has been used that are provided in this data file. All original core data (GLAD6 BOS04 5B) can be also found at doi:10.1594/PANGAEA.969452. These have been retrieved in a ~4 cm resolution by the Continental Scientific Drilling Facility at the University of Minnesota, USA using a Geotek MSCL-S multisensor core logger equipped with a 3-inch diameter NaI(Tl) detector housed in a 6-inch diameter lead shield. All data are reported as total counts, integrating all emission counts over the gamma ray energy range between 0 and 3 MeV. For these measurements the archive core half has been used. Measurement uncertainties range between 5 and 10%.